Study of corrosion rate and accumulation of deposits under circulating water concentration in bench experiments - Чиченин, Вадим Валентинович; Кишневский, Виктор Афанасьевич; Грицаенко, Анастасия Сергеевна; Ахрамеев, Виталий Геннадиевич; Шуляк, Ирина Дмитриевна (Eastern-European Journal of Enterprise Technologies, 2015)
The results of the study of corrosion rate and accumulation of deposits on the equipment of circulating cooling systems (CCS) fed with biologically treated municipal and industrial wastewater in the circulating water inhibition by phosphonate-based reagents were presented. Methods of testing the corrosion intensity, the formation of sparingly soluble deposits from carbonates and corrosion products on heated and unheated samples of various metals in the circulating water inhibition were given. Stands for investigating low-temperature scale formation and corrosion of structural materials of power equipment, simulating thermal-hydraulic operating conditions of circulating cooling systems of large power facilities to conduct a series of experiments on samples of different metals were developed. Comparisons of the results of physicochemical composition of deposits based on X-ray phase analysis, gravimetric, chemical control on test samples, and the corrosion intensity of the St.20 samples show the comparability of the results obtained after 100...150 hours of testing. However, at longer tests, the total amount of deposits on samples, obtained by gravimetric control is lower than the mass loss due to corrosion, which is explained by metal dissolution in the circulating water and low adhesion of the corrosion products with the sample surface. The data are needed to predict the management efficiency of water chemistry of the cooling systems of large power facilities fed with make-up high-salinity water by controlling the deposition intensity of sparingly soluble salts and corrosion on the heat transfer surfaces of power equipment.